2014
DOI: 10.1177/0003319714542277
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Contrast Media Volume–Glomerular Filtration Rate Ratio and Contrast-Induced Acute Kidney Injury After Primary Percutaneous Coronary Intervention

Abstract: We hypothesized that contrast media volume-estimated glomerular filtration rate (CV-e-GFR) ratio may be a predictor of contrast media-induced acute kidney injury (CI-AKI). We investigated the associations between CV-e-GFR ratio and CI-AKI in 597 patients undergoing primary percutaneous coronary intervention (pPCI). An absolute ≥0.3 mg/dL increase in serum creatinine compared with baseline levels within 48 hours after the procedure was considered as CI-AKI; 78 (13.1%) of the 597 patients experienced CI-AKI. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
17
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 33 publications
7
17
2
1
Order By: Relevance
“…The predictors of AKI in our propensity-matched sample were bleeding, heart failure, age ≥ 70 years, renal dysfunction on admission, and the contrast volume/GFR ratio, which is consistent with previously known data [2, 10, 20, 23, 3032]. These data would seem to support the presumption that AKI, in terms of the access site, might be at least partially influenced by confounding factors.…”
Section: Discussionsupporting
confidence: 91%
“…The predictors of AKI in our propensity-matched sample were bleeding, heart failure, age ≥ 70 years, renal dysfunction on admission, and the contrast volume/GFR ratio, which is consistent with previously known data [2, 10, 20, 23, 3032]. These data would seem to support the presumption that AKI, in terms of the access site, might be at least partially influenced by confounding factors.…”
Section: Discussionsupporting
confidence: 91%
“…The incidence of CI-AKI after pPCI ranges from 11.9 to 17.1% according to previous studies, which is significantly higher than that of elective PCI [19][20][21][22][23]. As with above studies, our study also demonstrated a similar high incidence of 15% in this population, which is strongly associated with blood volume insufficiency, hemodynamic instability and inadequate hydration.…”
Section: Discussionsupporting
confidence: 86%
“…Beside patient characteristics, procedural data and outcome characteristics were included in the multivariable regression model to elucidate the risk factors predicting AKI. As previously found, cardiogenic shock on admission, diabetes, hypertension, renal dysfunction, STEMI, heart failure [2, 5, 15, 17, 18], and contrast volume/eGFR ratio predicted AKI [5, 19]. In fact, this ratio seems to have a greater potential to discriminate between the patients who are at higher risk of AKI than the contrast volume alone since it includes 2 parameters (contrast volume and eGFR) that both predispose to AKI [19, 20].…”
Section: Discussionmentioning
confidence: 67%